Presence of aspergillus and other fungal symbionts in coffee beans from colombia (2012)
Fungi are common inhabitants of plants and plant-derived products. Some of these fungal species are potentially dangerous to human health since they are able to produce chemical substances that alter normal physiological activity. There are no studies about natural mycoflora associated with coffee beans in Colombia, and nothing is known about the presence and abundance of toxigenic fungal species in Colombian coffee. In this study 5,000 coffee beans were studied by plating them on potato-based artificial culture medium and it was shown that potentially toxigenic fungal taxa (mostly from genera Aspergillus, Fusarium, Penicillium), are currently found in Colombian coffee beans. This is true for all steps of coffee processing, from berries in trees to toasted grains, including packed coffee ready for retail in supermarkets. Results show that the distribution of these fungi is not random among different steps of coffee processing, which means that some steps are more vulnerable to infection with some fungi that others. The convenience of establishing a program devoted to detect fungi and/or mycotoxins in Colombian commodities, specially coffee, is discussed here.